Comparison of lung cancer aggressiveness in patients who never smoked compared to those who smoked. (September 2022) - Adler, Shoshana; Yip, Rowena; Chan, Huiwen; Cai, Qiang; Zhu, Yeqing; Triphuridet, Natthaya; Kaufman, Andrew; Taioli, Emanuela; Flores, Raja; Henschke, Claudia I.; Yankelevitz, David F.; ,
Highlights: Never smokers had significantly lower SUVmax and longer VDT compared to smokers. No difference in SUVmax and VDT by smoking status after adjusting for histology. Management and screening intervals should be identical, regardless of smoking history. Abstract: Objectives: To determine whether radiographic measures of tumor aggressiveness differ by smoking status. Materials and Methods: All patients diagnosed with non-small-cell lung cancer(NSCLC) ≤ 30 mm in maximum diameter, without clinical evidence of metastasis who had both pre-treatment PET scans and two CT scans at least 90 days apart in a prospective cohort, the Initiative for Early Lung Cancer Research on Treatment(IELCART) at Mount Sinai between 2016 and 2020 were identified. Comparison of two measures of tumor aggressiveness, positron emission tomography(PET) SUVmax and tumor volume doubling time(VDT) by smoking status was performed. Results: Of 417 patients identified, 158 patients had pre-treatment PET scans and at least two CT scans available. The two measures of tumor aggressiveness, SUVmax and VDT values were significantly different between patients who had never smoked and those who smoked: patients who never smoked had lower median SUVmax[2.5(IQR: 1.1–4.8) vs. 4.2(IQR:2.1–9.2), p = 0.002] and longer median VDT[(372.6 days vs. 225.6 days, p = 0.001)] compared to those who smoked. Using multivariable analyses, when adjusting for age and sex alone, SUVmax(p = 0.004) and VDT(p = 0.0001) remained significantly different by smoking status. The final multivariable analysis, adjusted for all three co-variates(sex, age and tumor histology) showed no significant difference in SUVmax and VDT by smoking status [SUVmax(p = 0.25) and VDT(p = 0.06)]. Conclusion: Smoking history does not influence VDT or PET SUVmax measures of lung cancer aggressiveness.